Analysis of Motivation and Mathematics Learning During the Covid-19 Pandemic - Rinda Azmi Saputri (Department of Mathematics Education University of Muhammadiyah Malang, 2022)
The purpose of this study was to analyze learning motivation in mathematics learning, analyze mathematics learning and the relationship between student learning motivation and mathematics learning during the covid-19 pandemic at Hulu Sungai Selatan District High School. The type of research used is descriptive with a quantitative approach. The population in this study were students and several mathematics teachers at the Hulu Sungai Selatan District High School. The samples of this study were 100 students and five teachers taken from five high schools in Hulu Sungai Selatan Regency. This sampling technique uses cluster random sampling/area random sampling. The results of this study are student motivation at SMAN 1 Daha Utara is in the high category with a percentage of 78.3%, student motivation at SMAN 1 Daha Barat is in the high category with a percentage of 76.5%, student motivation at SMAN 1 Kandangan is in the high category. in the high category with a percentage of 78%, student motivation at SMAN 1 Angkinang is in the high category with a percentage of 77.8%, student motivation at SMAN 1 Simpur is in the high category with a percentage of 76.3%. As for mathematics learning carried out by teachers, each teacher at school must use whatsapp as a learning medium, but there are also some teachers who use other media to help learning mathematics such as google classroom, zoom/gmeet, learning videos and power point. The relationship between students' learning motivation and mathematics learning is that the more media used by the teacher, the higher the learning motivation